Badan Permusyawaratan Desa Dalam Tiga Periode Pemerintahan Di Indonesia - Emilda Firdaus (Jurnal Ilmu Hukum, 2011)
Historically village represent will form of political society and the governance in Indonesia far before this nation and state is formed. Social structure of a kind the village, socialize custom and others have come to social institution having very important position. In order to to realize autonomy and democratize at the village governance, hence need there is clear arrangement and this specially to existence BPD in each regency in Indonesia. In three governance period in Indonesia that is from Orde Lama period, period of Orde Baru and  Reform Order  have acknowledged legislative body and village governance system of village although own difference in the form of it implemented.